The right of party participation as one of the political rights of citizens Analytical - Comparative Study - امىدرس امدكخِر ڕیتیي شالم وحىد شػید,; امىدرس امىصاغد ًٍَِر غتدامرحىي شػيد, (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
A citizen is a person who settles in a certain land and belongs to it. And this citizen is a party to a relationship between individuals and the state determined by the law of the state, since citizenship cannot be achieved without a citizen who fully understands his rights and duties of the homeland, and that, there is no citizenship without a citizen, and there is no citizen without a genuine participation in the affairs of the nation on various levels and aspects. One of the most important collective types of political rights is the right of participation in political parties and pressure groups /lobbies. In a modern sense Political parties are a newly developing phenomenon. However, parties have their historical origins, which are represented in opinion trends, popular associations, think tanks and parliamentary groups. In the past, these parties, and other similar ones were considered an unholy heresy, indicative of discrimination and feared for the unity of the state and viewed with some discomfort. And, in modern times, the parties emerged with the spread of the principle of universal suffrage in the nineteenth century. Consequently, electorates who were now political rights holders found themselves unable to discuss their problems or set their target, and this created the need for the establishment of popular organizations that people could turn to. In this way, political parties have emerged. In other words, political parties have responded to the need of voters. They have developed programs that will collect as many votes in favor of its candidates in order to obtain a majority of parliamentary seats so that they can form or contribute to the formation of the Government.Times New Roman as a Font Type and Font Size is 12.